The history and evolution of the back squat in the United States - Heffernan, C. (Strength and Conditioning Journal, 2025)
This article provides the first academic history of the barbell back squat and its evolution from a bodyweight exercise in the 19th century to a loaded exercise, used for a variety of purposes, in the present age. In doing so, the article highlights 3 key drivers in the evolution of the back squat - those being changes in equipment, the diversification of strength sports, and scientific communication concerning the safety and efficacy of the movement. The goal of this article was not to provide a dry and irrelevant history but rather to stress the complexity of the squat's prominence within fitness programs and the need to hold a nuance view toward the "optimal" way to approach this movement. In doing so, it examines how the movement evolved from 1 primarily done on the tips of one's toes, to a loaded movement on tippy toes, to a flat footed movement. By contextualizing the back squat's history, this article challenges rigid notions of "correct" squatting technique and encourages a more nuanced understanding of exercise selection in strength and conditioning practice. It concludes by highlighting the importance of critically examining the social construction of knowledge in fitness and sport, and the value of historical perspective in informing contemporary training practices.